PENGARUH KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI DINAS SEKRETARIAT DAERAH KOTA LANGSA - Popriana Popriana; Dhian Rosalina; Dewi Rosa indah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine the effect of intellectual intelligence and emotional intelligence on the performance of employees of the Regional Secretariat Office of Langsa City. The method used in this research is quantitative method using the help of SPSS 26. The population in this study amounted to 71 employees. And the sample in this study amounted to 71 employees. The sampler in this study was non probability sampling with saturated sampling technique. the data analysis method used in this study is t test, F test. The results of this study indicate the results of regression analysis with the equation Y = 5.036 + 0.256 X1 + 0.442 X2. The result of the t test for the effect of intellectual intelligence (X1) on performance (Y) is 2.500 and the t-sig is smaller than the alpha value of 0.015 <0.05, for emotional intelligence (X2) on performance (Y) is 7.001 and the t sig value is smaller than the alpha value of 0.000 <0.05. And for the F test with a significance value of 0.000 <0.05. And for the F test with a significance value of 0.000 <0.05.